A High Power Factor Hybrid three-phase Rectifier with Regenerative Capability - Carlos Henrique Illa Font; Ivo Barbi (Eletrônica de Potência)
This paper presents theoretical analysis and experimentation of a hybrid three-phase rectifier suitable for medium and high power applications. The hybrid rectifier is formed by the parallel connection of a three-phase diode bridge rectifier cascaded by a DC-DC boost converter and a bidirectional boost-type three-phase PWM rectifier. The proposed rectifier is capable of providing sinusoidal input currents, DC output voltage control and regenerative power flow. Furthermore, the parallel association of different three-phase rectifier topologies provides power distribution, allowing the use of lower cost switches. The principle of operation, the theoretical analysis, the control scheme, simulation and experimental results from a 20-kW prototype are presented. The prototype was designed for a 380V of input voltage, 700V of output voltage and switching frequency of 10kHz.